EFEKTIVITAS MICROLEARNING TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Jasmine, Annisa; Angger Wardhani, Prayuningtyas; Fahrurrozi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has encouraged the implementation of microlearning, which delivers learning content in short and focused units. This approach is considered suitable for elementary school students who generally have shorter attention spans. This study aims to analyze the effectiveness of microlearning on elementary school students' learning outcomes using a literature review method. Data were collected from national and international journal articles published between 2019 and 2025 through Google Scholar, Scopus, ERIC, ScienceDirect, SpringerLink, and Taylor & Francis Online. The data were analyzed using content analysis by identifying, selecting, and synthesizing relevant studies. The findings indicate that microlearning effectively improves students' learning outcomes, including conceptual understanding, learning motivation, knowledge retention, and student engagement. Its effectiveness is influenced by instructional design, interactive digital media, teachers' competencies, and technological support. Therefore, microlearning can be considered an innovative learning strategy to enhance the quality of learning in elementary schools.